Life and death at Paloma : society and mortuary practices in a preceramic Peruvian village - Quilter, Jeffrey, 1949- (University of Iowa Press, 1989)
Life and Death at Paloma, when published in 1989, was the first in-depth treatment of burials from a preagricultural South American village. It remains a valuable resource used by students and scholars of Andean archaeology. Jeffrey Quilter analyzes the life of Paloma's people during the transition from a hunting-gathering-fishing way of life to a more sedentary horticultural society and offers a study of preceramic Peruvian life through his analysis of this site's graves and their contents.